Evaluating Clustering Algorithms for Optimized Performance in Wireless Sensor Networks (Journal of Academic Research, 2025)
Wireless Sensor Network (WSN) has gradually become an essential technology in recent years and is employed in various fields. One of the main challenges of WSNs is their short lifespan; due to the energy consumption which is affected by communication protocols, packet data transfer, and limited battery power factors. And among these factors, many researchers are interested in energy efficiency. In this paper, a new enhanced LEACH routing technique has been proposed. The proposed technique selects cluster heads based on current energy, and it employs a root cluster head with greater current energy and a short distance to the sink to gather all data before sending them to the sink. The results exposed that the proposed technique is outperformed the standard LEACH protocol and extended the WSN network lifespan.